PENGARUH PERBANDINGAN KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL 3 VARIETAS CABAI RAWIT (Capsicum annuum L. - Fransiska Ayu; Tantri Swandari; Titin Setyorini (Program Studi Agroteknologi INSTIPER, 2019)
The aims of this research is to determine the effect of the comparison of the composition of the planting media on the growth and yield of three varieties of cabai rawit (Capsicum annuum L). This research was conducted in Maguwoharjo Village, Depok District, Sleman Regency, Yogyakarta. The research was conducted from March to June 2019 using refusal soil and manure. This study used a factorial method, which was arranged in a completely randomizing design (RAL) with 2 factors. The first factor is the ratio of the composition of the planting medium (manure: soil) with a level of 1: 1, 1: 3, 3: 1, and control. The second factor is the varieties of cabai rawit such us Dian F1, Sret and Sigantung. The results showed that there was no interaction between the comparison of the composition of the planting medium and three varieties of cabai rawit on each parameter, but had a significant effect on several parameters. Comparison of the composition of the planting medium has a significant effect on the growth and yield. Planting medium, that contain manure: soil (1:1) had a significant effect on the parameters of the number of fruits and the weight of the fruit, while the 1: 3 ratio of the planting medium had a significant effect on the parameters of the fresh root weight and the root length. Dian-F1 variety showed the best growth response and yield. Keyword : planting medium, manure, growth, yield, cabai rawit